Designers' Cognitive Thinking Based on Evolutionary Algorithms - Zhang Shutao; Jianning Su; Chibing Hu; Peng Wang (Institute of Advanced Engineering and Science, 2014)
The research on cognitive thinking is important to construct the efficient intelligent design systems. But it is difficult to describe the model of cognitive thinking with reasonable mathematical theory. Based on the analysis of design strategy and innovative thinking, we investigated the design cognitive thinking model that included the external guide thinking of